Family in the structure of social and public education in Ukraine - Zavgorodnâ, Tetiana K. (Oficyna Wydawnicza ATUT - Wrocławskie Wydawnictwo Oświatowe, 2012)
Basic negative phenomena present among the youth of the contemporary Ukrainian society are discussed in the article. An attempt has been made to identify their causes. While defining the functions of the family and analysing the positive experiences connected with education within the family in the structure of citizenship education and public education the methods of overcoming problems and increasing the role of the family that should thoroughly fulfil its educational role in the contemporary world - a role which consists in educating true citizens of independent Ukraine - have been discussed.
Keywords: family; public education; state education; forms of work; parents; young families